Kebebasan Belajar dalam Konsep Summerhill dan Kebebasan Berpikir dalam Islam: Suatu Kajian Komparatif - Zacky Al-Ghofir El-Muhtadi Rizal (EDUCATIVA, 2025)
This paper analyzes freedom of learning in the Summerhill concept and freedom of thought in Islam through a qualitative comparative study. The purpose of this study is to analyze the similarities and differences between the two concepts of freedom in the context of education and thought. Summerhill, developed by A.S. Neill, offers complete freedom for students to choose subject matter and learning activities, with an emphasis on developing independent individuals through freedom of decision-making. In contrast, in Islam, freedom of thought is seen as a God-given right, yet still bound to moral and spiritual principles set out in divine revelation. This research utilizes a qualitative comparative study. The results of this study reveal that although freedom in Summerhill and freedom of thought in Islam have some similarities in terms of encouraging individual development, they differ in the way such freedom is regulated and applied. An understanding of these two concepts provides deeper insights into how freedom can be understood and applied in education to form independent and socially, morally and spiritually responsible individuals.